An experimental investigation on freezing and thawing durability of high performance fiber reinforced concrete (HPFRC). (15th February 2020) - Feo, L.; Ascione, F.; Penna, R.; Lau, D.; Lamberti, M.
Abstract: This study presents the results of an experimental investigation on the durability of a commercial High Performance Fiber Reinforced Concrete (HPFRC) subjected to rapid freeze/thaw cycles. High-performance fiber reinforced concrete (HPFRC) is currently being used in the construction industry both for strengthening existing members and for controlling opening cracks in new ones. In literature there are many studies focused on the evaluation of the HPFRC mechanical properties varying the matrix composition and/or the type and quantity of the fibers but a lack of knowledge exists for what concerns its durability. Durability of concrete may be defined as the ability of concrete to resist weathering conditions, chemical attack and abrasion while maintaining its desired engineering properties. In particular, durability can be defined by the percentage ratio of the dynamic modulus of elasticity after a number of freeze and thaw cycles to the corresponding value before the freeze and thaw cycles. In this paper, three different concrete mixtures with various fiber volume fraction, i.e. 0%, 1.25% and 2.50%, were examined. Seventy-five freeze-thaw cycles were performed according to UNI 7087-2017 on five prismatic specimens per each concrete mixture while other three specimens were selected as reference samples. In order to evaluate the durability factor of the three mixture, the resonant frequencies (transversal, longitudinal and torsional) and the dynamic moduli of elasticity were measured using the Impact Resonance Method (IRM) provided by the ASTM C215.